Microstructure, Chemical Bonds, and Photocatalyst Activity of Neodymium-doped Strontium Titanate (Sr0.97Nd0.03TiO3) with 900°C and 1000°C Sintering Temperature. Issue 1 (1st December 2022) - Hasanah, L U; Agustina, F R; Puspita, N F S; Suherman, B; Nurosyid, F; Sandi, D K; Iriani, Y
Abstract: Strontium Titanate is a perovskite oxide with remarkable properties as a photocatalyst. The synthesis of Strontium Titanate material with Neodymium doping (Sr0.97 Nd0.03 TiO3 ) has been completed by means of the co-precipitation procedure. Samples were sintered at temperatures of 900°C and 1000°C for 4 hours to investigate their properties. X-Ray Diffraction (XRD), Fourier-Transform Infrared spectroscopy (FTIR), and UV-Vis Spectrophotometer were employed to observe the microstructure, chemical bonds, and photocatalyst activity of Sr0.97 Nd0.03 TiO3 . XRD data exhibited that the crystal size enlarged from 42.3 nm and 64.4 nm as the sintering temperature increased. FTIR data revealed strong Sr-Ti-O bonds and decreased C-H and C=H bond impurities as the sintering temperature increased. The photocatalytic performance was evaluated with methylene blue (MB) dye degradation by UV light irradiation for 3, 4, and 5 hours where the UV-Vis spectrophotometer tested the absorbance of the degraded MB. The results exhibited that Sr0.97 Nd0.03 TiO3 achieved the optimal degradation (62.7%) at 900°C and with 3 hours of irradiation.